Approach to the Patient with an Adrenal Incidentaloma - Nieman, Lynnette K. (The Endocrine Society, 2010)
Unsuspected adrenal masses, or incidentalomas, are increasingly found with the widespread use of thoracic and abdominal imaging. These masses may be hormonally active or nonfunctional and malignant or benign. Clinicians must determine the nature of the mass to decide what treatment, if any, is needed. Measurement of precontrast Hounsfield units (HU) and contrast washout on computed tomography scan provide useful diagnostic information. All patients should undergo biochemical testing for pheochromocytoma, either with plasma or urinary catecholamine measurements. This is particularly important before surgical resection, which is routinely recommended for masses larger than 4 cm in diameter without a clear-cut diagnosis and for others with hormonal secretion or ominous imaging characteristics. Hypertensive patients should undergo biochemical testing for hyperaldosteronism. Patients with features consistent with Cushing’s syndrome, such as glucose intolerance, weight gain, and unexplained osteopenia, should be evaluated for cortisol excess. Here, the dexamethasone suppression test and late-night salivary cortisol may be preferred over measurement of urine cortisol. The ability of surgical resection to reverse features of mild hypercortisolism is not well established. For masses that appear to be benign (<10 HU; washout, >50%), small (<3 cm), and completely nonfunctioning, imaging and biochemical reevaluation (pheochromocytoma and hypercortisolism only) at 1–2 yr (or more) is appropriate. For more indeterminate lesions, repeat evaluation for growth after 3–12 months is useful, with subsequent testing intervals based on the rate of growth.